Implementation of Augmented Reality-Based Learning Media to Increase Students' Interest and Understanding of Plant Anatomy Materials - oyyibah, Hayatun Toyyibah (Journal of Educational Studies, 2024)
This study aims to explore the implementation of Augmented Reality (AR)-based learning media in increasing students' interest and understanding of plant anatomy material. The method used is a quasi-experiment with a pretest-posttest design. This study involved grade III students in one of the elementary schools in MI NW Keruak. The results showed that the use of AR-based learning media significantly increased students' interest which was reflected in increased enthusiasm, engagement in discussions, and frequency of asking questions during learning. In addition, test results show a significant improvement in students' understanding of plant anatomical concepts, such as the structure and function of plant organs. The use of interactive 3D models allows students to more easily understand abstract material. Thus, the application of AR technology in learning can be an effective alternative to improve the quality of science learning, especially in materials that require strong visual understanding. This research contributes to the development of more innovative and contextual learning methods, as well as offering insights into the use of technology in education.